Screening of antibiotic residues in chicken meat in Bangladesh by thin layer chromatography - Sarker, Yousuf Ali; Hasan, Md. Mehedi; Paul, Torun Kumar; Rashid, Sm. Zamiul; Alam, Md. Nurul; Sikder, Mahmudul Hasan (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Screening of antibiotic residues in broiler chicken meat and liver collected from farms and local markets in Bangladesh. Materials and methods: A total of 160 samples (breast, thigh muscle and liver) were collected from markets and farms from different region of Bangladesh. PBS buffer system with trichloracetic acid and diethyl ether based sample extraction was performed. For comparison the standard antibiotics; Ciprofloxacin (CIP), Enrofloxacin (ENR), Oxytetracycline (OTC), Amoxicillin (AMOX) and Doxycycline (DOX) were prepared by dissolving in methanol. Samples were pointed on TLC plates transferred to TLC tank containing acetone-methanol (1:1) as mobile phase. Retention factor (Rf) was calculated after observing the chromatograms on UV light at 256 nm. Same Rf value of standard and sample considered similar compound. Results: Liver sample were mostly positive for antibiotics residue followed by thigh muscles and breast muscle. The frequency of antibiotic residues was highest in liver followed by thigh muscles and breast muscle. Among the antibiotics CIP ranked top in all types of sample. In breast muscle highest antibiotic was CIP (39%) followed by DOX (26%), AMOX (24%), OTC (23%) and lowest was ENR (21%). In thigh muscle, 42, 29, 28, 27 and 24% sample was positive for CIP, OTC, DOX, AMOX and ENR, respectively. Highest number of liver samples were shown positive result for all screened antibiotics (CIP-52%, OTC-46%, DOX-43%, AMOX-42% and ENR-36%). Conclusion: This study ascertained those antibiotics residues are present in chicken muscle and liver which causes serious health hazards to consumers. So proper steps should be taken to control emergence of antibiotic resistance in human being as well as in the environment. http://doi.org/10.5455/javar.2018.e257